Differences in small intestinal apparent amino acid digestibility of raw bovine, caprine, and ovine milk are explained by gastric amino acid retention in piglets as an infant model - Ahlborn, Natalie G.; Montoya, Carlos A.; Roy, Debashree; Roy, Nicole C.; Stroebinger, Natascha; Ye, Aiqian; Samuelsson, Linda M.; Moughan, Paul J.; McNabb, Warren C. (Frontiers in Nutrition, 2023)
Background The rate of stomach emptying of milk from different ruminant species differs, suggesting that the small intestinal digestibility of nutrients could also differ across these milk types. Objective To determine the small intestinal amino acid (AA) digestibility of raw bovine, caprine, and ovine milk in the piglet as an animal model for the infant. Methods Seven-day-old piglets (n = 12) consumed either bovine, caprine, or ovine milk diets for 15 days (n = 4 piglets/milk). On day 15, fasted piglets received a single meal of fresh raw milk normalized for protein content and containing the indigestible marker titanium dioxide. Entire gastrointestinal tract contents were collected at 210 min postprandially. Apparent AA digestibility (disappearance) in different regions of the small intestine was determined. Results On average, 35% of the dietary AAs were apparently taken up in the small intestine during the first 210 min post-feeding, with 67% of the AA digestibility occurring in the first quarter (p ≤ 0.05) and 33% in the subsequent two quarters. Overall, except for isoleucine, valine, phenylalanine, and tyrosine, the small intestinal apparent digestibility of all AAs at 210 min postprandially in piglets fed ovine milk was, on average, 29% higher (p ≤ 0.05) than for those fed bovine milk. Except for lysine, there was no difference in the apparent digestibility (p > 0.05) of any AAs between piglets fed caprine milk or ovine milk. The apparent digestibility of alanine was higher (p ≤ 0.05) in piglets fed caprine milk than those fed bovine milk. When apparent digestibility was corrected for gastric AA retention, only small differences in the small intestinal apparent digestibility of AAs were observed across milk types. Conclusion Bovine, caprine and ovine milk had different apparent small intestinal AA digestibility at 210 min postprandially. When corrected for gastric AA retention, the differences in apparent digestibility across species largely disappeared. The apparent AA digestibility differed across small intestinal locations.